Impacts of vacancy-induced polarization and distortion on diffusion in solid electrolyte Li3OCl. (29th November 2021) - Mehmedović, Zerina; Wei, Vanessa; Grieder, Andrew; Shea, Patrick; Wood, Brandon C.; Adelstein, Nicole
Abstract : Lithium-rich oxychloride antiperovskites are promising solid electrolytes for enabling next-generation batteries. Here, we report a comprehensive study varying Li + concentrations in Li 3 OCl using ab initio molecular dynamics simulations. The simulations accurately capture the complex interactions between Li + vacancies (V Li ′ ), the dominant mobile species in Li 3 OCl . The V Li ′ polarize and distort the host lattice, inducing additional non-vacancy-mediated diffusion mechanisms and correlated diffusion events that reduce the activation energy barrier at concentrations as low as 1.5% V Li ′ . Our analyses of discretized diffusion events in both space and time illustrate the critical interplay between correlated dynamics, polarization and local distortion in promoting ionic conductivity in Li 3 OCl . This article is part of the Theo Murphy meeting issue 'Understanding fast-ion conduction in solid electrolytes'.